Reading of Imam Al-A’mash (may Allah have mercy on him) in the interpretation of Ibn Atiya. Surat Al-Baqarah as an example - collection and study (Islamic Sciences Journal, 2024)
ABSTRACTImam Al-A'mash is considered a transmitter of reading, and he transmits correct and abnormal readings. Although most of the readings he narrated agree with the reading of the ten imams of readings, he transmits abnormal readings according to the evidence or choice available to him, even though scholars have documented him. His narrations of reading have been collected in Tafsir Ibn Atiyyah. Surah Al-Baqarah is an example, and I found it in eighteen places, and I divided it into two parts, the correct and the irregular. I divided the research into three tasks. The first requirement was to introduce the life of Imam Al-A’mash. The second requirement was for the correct readings that he narrated, which were twelve letters. I made the third requirement for the irregular readings in which he narrated. Six letters, and I translated the flags according to the occurrence of each flag and mention it the first time. I did not indicate the page number on which I mentioned its translation the first time when mentioning it again for fear of lengthening or burdening the margins. Evidence for some of the readings that were narrated with abnormalities was not available from the books of proofs, and I adopted the approach. Statistics and comparison in research, and from God, success.
Keywords: Readings, reading, recitation, irregular reading, intonation